A comparative study of target contolled infusion (TCI) and manual controlled infusion (MCI) of propofol for sedation in severe traumatic brain-injured patient - W Hassan, W Mohd Nazaruddin (Pusat Pengajian Sains Perubatan, Universiti Sains Malaysia, 2010)
Background. The aims of this study are to compare TCI with MCI propofol as sedation in severe traumatic brain-injured (TBI) patients. Methods. Post emergency craniotomy for severe TBI patients (n = 50), were randomly assigned to receive propofol sedation over 24 hours using two modes of infusion: TCI versus MCI (n = 25 in each groups). Sedation was monitored using bispectral index \BIS) monitor and sedation agitation scale (SAS). TCI was titrated between 0.2-2.0 llg mr and MCI was between 0.3-4.0 mg kg·1 h"1 to achieve sedative state at BIS 60-70 and SAS 2-3. Mean arterial pressure (MAP), heart rate (HR), intracranial pressure (ICP), cerebral perfusion pressure (CPP), time taken and volume used to achieve BIS 70, total volume of propofol over 24 hours and recovery time to BIS 90 were recorded. Results. TCI achieved BIS 70 significantly faster than MCI (6.3 ± 2.9 min vs. 19.7 ± 7.0 min). Total volume of propofol at BIS 70 was significantly less in TCI (12.0 ± 2.9 ml vs.l7.8 ± 4.3 ml). Recovery time to BIS 90 was also significantly faster in TCI (24.4 ± 11.5 min vs. 57.3 ± 19.9 min). TCI showed significantly lower in HR and ICP trends over 24 hours. CPP trends were significantly higher in TCI. There were no significant differences in MAP and total volume over 24 hours. Conclusions. TCI modes had more advantages for propofol sedation in TBI by providing faster onset and offset of sedation and better in controlling ICP and CPP.